Rancang Bangun Automatic Transfer Switch (ATS) Automatic Main Failure (AMF) Menggunakan PLC LS Master K120s - Dwi Harjono; Tri Jaka Satria; Nurhaidah Nurhaidah (Jurnal ELIT, 2022)
The need for a reliable and continuous power source to supply electrical loads is very important. In order for continuous electricity supply, a system of Automatic Transfer Switch - Automatic Main Failure (ATS - AMF) is needed. This system will automatically divert electrical power from the main PLN source to a backup source. The stages in the design of this tool include ATS-AMF planning, component assembly process, and box panel assembly. The result is a 380 V, 50 Hz ATS/AMF panel based on the LS Master K120s PLC which is supported by both manual and automatic operating systems. For the AMF system using the PLC LS Master K120s, the generator set is set for 3 seconds after the supply from PLN goes out and will immediately supply electrical energy after 5 minutes after the generator is running. When PLN returns to normal for 5 minutes the generator set will be separated from the system, the generator will cool down, then the generator will stop. The ATS-AMF system works as described for which it was designed.